Exploring medical students’ perceptions of the challenges and benefits of volunteering in the intensive care unit during the COVID-19 pandemic: a qualitative study - Seamus Sreenan; Arnold Hill; Aliya Ali; Marita Staunton; Adam Quinn; Gordon Treacy; Patrick Kennelly; Marian Brennan (BMJ Open)
Objectives In March 2020, the WHO declared SARS-CoV-2 a pandemic. Hospitals across the world faced staff, bed and supply shortages, with some European hospitals calling on medical students to fill the staffing gaps. This study aimed to document the impact of volunteering during the COVID-19 pandemic on students’ professional development, resilience and future perceived career choices.Design This is a retrospective, qualitative study of student reflections, using purposive sampling.The Royal College of Surgeons in Ireland (RCSI) University of Medicine and Health Sciences recruited 26 medical student volunteers to assist in pronation and supination of ventilated patients affected by SARS-CoV-2. These students were invited to complete an anonymous survey based on their experiences as volunteers. Thematic analysis was performed on these written reflections.Results The results showed that volunteering during the COVID-19 pandemic developed key skills from RCSI’s medical curriculum, significantly fostered medical students’ resilience and guided their career choices. Major areas of development included communication, teamwork, compassion and altruism, which are not easily developed through the formal curriculum. A further area that was highlighted was the importance of evidence-based health in a pandemic. Finally, our respondents were early stage medical students with limited clinical exposure. Some found the experience difficult to cope with and therefore supports should be established for students volunteering in such a crisis.Conclusion These results suggest that clinical exposure is an important driver in developing students’ resilience and that volunteering during a pandemic has multiple benefits to students’ professional development and professional identity formation.